A decade of data from a specialist statewide child and adolescent eating disorder service: does local service access correspond with the severity of medical and eating disorder symptoms at presentation? - Alman, Jeremy; Hoiles, Kimberley; Watson, Hunna; Egan, Sarah; Hamilton, Matthew; McCormack, J.; Potts, J.; Forbes, D.; Shu, Chloe (BioMed Central, 2014)
Background - Eating disorders affect up to 3% of children and adolescents, with recovery often requiring specialist treatment. A substantial literature has accrued suggesting that lower access to health care services, experienced by rural populations, has a staggering effect on health-related morbidity and mortality. The aim of this study was to evaluate whether lower service access foreshadowed a more severe medical and symptom presentation among children and adolescents presenting to a specialist eating disorders program. Method - The data source was the Helping to Outline Paediatric Eating Disorders (HOPE) Project registry (N ~1000), a prospective ongoing registry study comprising consecutive paediatric tertiary eating disorder referrals. The sample consisted of 399 children and adolescents aged 8 to 16 years (M =14.49, 92% female) meeting criteria for a DSM-5 eating disorder. Results - Consistent with the hypotheses, lower service access was associated with a lower body mass index z-score and a higher likelihood of medical complications at intake assessment. Contrary to our hypothesis, eating pathology assessed at intake was associated with higher service access. No relationship was observed between service access and duration of illness or percentage of body weight lost. Conclusions - Lower service access is associated with more severe malnutrition and medical complications at referral to a specialist eating disorder program. These findings have implications for service planning and provision for rural communities to equalize health outcomes.